Direct observation of surface polarization at hybrid perovskite/Au interfaces by dark transient experiments - Caram, Jorge Pablo (2020)
A distinctive feature of hybrid perovskite light-absorbing materials is the non-negligible ionic conductivity influencing photovoltaic performance and stability. Moving ions or vacancies can naturally accumulate at the outer interfaces (electrode polarization) upon biasing. Contrary to that approach, a modulation of conductive or recombination properties could manifest as an alteration in the low-frequency part of the impedance response, either producing inductive or large capacitive features. Under this last view, capacitances are not the response of polarized structures or charging mechanisms, but result from the modulation of currents. This work intends to provide pieces of evidence that assist us in distinguishing between these two dissimilar mechanisms, namely, real charge polarization and delayed current effects under bias in the dark. The analysis relays upon an experimental technique based on transient charging signals using the Sawyer-Tower circuit. Instead of applying an alternating small perturbation over a steady-state voltage (differential capacitance method), transient charging measures the resulting polarization upon a large bias step under the suppression of dc currents. Our findings reveal that real steady-state charge is indeed induced by the applied voltage in the dark, easily interpreted by means of charged real capacitors with values much larger than the geometrical capacitance of the film. The connection between that polarization and the charging of perovskite/contact interfaces is highlighted.